Perceptions of the inhabitants of the municipality of Sabaneta regarding changes in air quality and its influence on public health between 2015-2020 - Rincón Largo, Jorge Andrés; Vahos Mosalve, Diego León (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2023)
Objective: The purpose of the research was to determine the perception that the inhabitants of the municipality of Sabaneta have of the changes in air quality in the last five years and how they influence their health and well-being. Methodology: A qualitative, descriptive, retrospective, retrospective, cross-sectional and observational research design was determined; the study population was constituted by the inhabitants of the municipality of Sabaneta, with a selected sample of 24 inhabitants for the application of the interview. Results: As a result of the research, the following perceptions were found: 100% said that in the last five years there has been a significant change in the quality of the air in the municipality; 100% said that air pollution affects their health and that of their families; 50% of those interviewed think that it affects only respiratory health, 33% said that in addition to respiratory health it affects visual health and 17% that it also affects skin health; For those interviewed, the main factors of this problem are the increase in the number of vehicles (42%), the increase in population (17%), the increase in civil constructions (17%) and the industrial sector (25%). Conclusion: In conclusion, some control guidelines are determined that are peremptory to minimize the emission of criteria pollutants in the municipality of Sabaneta.